Control of Active Magnetic Bearings in Turbomolecular Pumps for Rotors with Low Resonance Frequencies of the Blade Wheel - Markus Hutterer; Manfred Schrödl (Lubricants, 2017)
Rotors with high gyroscopic effects and low resonance frequencies caused by the blade wheel (blade frequencies) can lead to stabilization problems in the application field of turbomolecular pumps. If such a rotor is stabilized by active magnetic bearings, the control structure could be destabilized by the splitting up of the rigid body eigen-frequencies caused by the gyroscopic effect. The control structure of the magnetic bearings can also destabilize the eigen-modes caused by the blade wheel, if the gain of the control structure is too high in the range of the eigen-frequencies of the blade wheel. To deal with the problem of the gyroscopic effect, a decoupling and compensation method was developed based on the inverse dynamics of the rigid body rotor. The gain of the control structure in the range of the blade frequencies is decreased using a Kalman filter. To increase the damping of the system, the predicted states of the linear magnetic bearing model using a Kalman filter are applied instead of the sampled values of the sensors directly. For the decoupled structure, PID controllers are used for stabilization. The functionality of the control structure is verified by a measurement of the current and position signal using the Kalman states and the sensor values. The robustness and performance in the frequency range are verified using the sensitivity and compliance function.